2017
DOI: 10.1177/0958928716685687
|View full text |Cite
|
Sign up to set email alerts
|

Campaigning on the welfare state: The impact of gender and gender diversity

Abstract: Social policy matters have long been considered women’s issues. Extant research has documented a strong link between gender and the policies of the welfare state in the legislative, executive and electoral arenas. Yet what determines the strength of this association has largely been left unexplored. Drawing on tokenism theory, this article proposes gender diversity at the group level as a key explanatory factor. It hypothesizes that the gender gap in social policy diminishes as the female representation in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
5
0
2
Order By: Relevance
“…46 This gender gap is not unique to New Zealand, and one political scientist recently concluded that there is "little on offer to clarify the circumstances that contribute to the strength of this relationship." 47 On the contrary, the American psychologist Carol Tavris made the argument twenty years ago that "the gender gap is largely an experience gap. More women than men today worry that they or their children might need a safety net if they lose a job, lose a partner or lose their health.…”
Section: Discussionmentioning
confidence: 99%
“…46 This gender gap is not unique to New Zealand, and one political scientist recently concluded that there is "little on offer to clarify the circumstances that contribute to the strength of this relationship." 47 On the contrary, the American psychologist Carol Tavris made the argument twenty years ago that "the gender gap is largely an experience gap. More women than men today worry that they or their children might need a safety net if they lose a job, lose a partner or lose their health.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, it should be noted that women have qualifications, experiences, and positions that differ from men, and, in a way, this directly influences their acceptance, which is significantly higher among female voters due to the positions that, generally, are due to women's rights and to issues related to health and family (Bhalotra & Clots-Figueras, 2014;Costa e Schaffner, 2018;Ennser-Jedenastik, 2017;Ng & Muntaner, 2018).…”
Section: Women In Politicsmentioning
confidence: 99%
“…In organizations of the political system, such as city councils and legislative assemblies, acceptance ends up becoming a critical component of this trajectory in the face of perceptions that power is something masculine (Araújo, 2010;Karawejczyk, 2013;Pinto & Silveira, 2018;Tosi, 2016) and because of the direction that women's actions can take in this scenario (Bhalotra & Clots-Figueras, 2014;Costa e Schaffner, 2018;Ennser-Jedenastik, 2017;Ng & Muntaner, 2018). In this context, it appears that microaggressions take on a greater proportion, being present in daily life not only organizationally, but also socially, as discussed below.…”
Section: From Identity Construction As a Woman In Brazilian Politics ...mentioning
confidence: 99%
“…Nesta mesma seara, Krook (2020) afirma que a violência contra as mulheres na esfera política acaba sendo menos reconhecida como um 'problema' e inclusive as próprias mulheres políticas que sofrem com suas consequências consideram-na como uma espécie de 'custo de se fazer política'. Contudo, salienta-se que as mulheres possuem qualificações, experiências e posicionamentos que diferem dos homens e, de certa maneira, isso influencia diretamente a sua aceitação, que é significativamente maior entre as mulheres eleitoras por conta dos posicionamentos que, geralmente, são em função dos direitos da mulher e em questões voltadas à saúde e família (Bhalotra & Clots-Figueras, 2014;Costa e Schaffner, 2018;Ennser-Jedenastik, 2017;Ng & Muntaner, 2018). Dessa forma, após expostos os conceitos que fundamentam este estudo, a seguir são especificados os procedimentos metodológicos utilizados nesta pesquisa.…”
Section: Mulheres Na Políticaunclassified
“…Em organizações do sistema político, como é o caso das Câmaras de Vereadores e Assembleias Legislativas, a aceitação acaba se tornando um componente crítico a essa trajetória diante das percepções de que o poder é algo masculino (Araújo, 2010;Karawejczyk, 2013;Pinto & Silveira, 2018;Tosi, 2016) e em virtude do rumo que a atuação das mulheres possa assumir nesse cenário (Bhalotra & Clots-Figueras, 2014;Costa e Schaffner, 2018;Ennser-Jedenastik, 2017;Ng & Muntaner, 2018). Nesse contexto, verifica-se que as microagressões tomam maior proporção, estando presentes no cotidiano não somente organizacional, mas também social, conforme se discorre a seguir.…”
Section: Da Construção Identitária Como Mulher Na Política Brasileira...unclassified